Dynamic mechanical behaviors of epoxy resin/hollow polymeric microsphere composite foams under forced non-resonance and forced resonance. (14th April 2021) - Li, Rui; Fan, Guisen; Ouyang, Xiao; Wang, Guojun; Wei, Hao
Composite foams with 10–50 vol% hollow polymeric microspheres were prepared using bisphenol A epoxy resin and polyetheramine curing agent as the matrix. The results demonstrated that the density, hardness, and static mechanical properties of the epoxy resin/hollow polymer microsphere composite foams, as well as their dynamic mechanical properties under forced non-resonance, were similar to those of polymer/hollow glass microsphere composite foams. At 25°C and under 1–100 Hz forced resonance, the first-order and second-order resonance frequencies of the composite foams shifted to the low-frequency region as the volume fraction of hollow polymer microspheres increased. Meanwhile, the first-order and second-order loss factors of the as-prepared composite foams were improved by 41.7% and 103.3%, respectively, compared with the pure epoxy resin. Additionally, the first-order and second-order loss factors of the as-prepared composite foams reached a maximum at 40 vol% and 30 vol% hollow polymer microspheres, respectively. This research helps us to expand the application range of composite foam materials in damping research.